Economic incentives for the adoption of electric vehicles: A classification and review of e-vehicle services. (December 2018) - Meisel, Stephan; Merfeld, Tanja
Highlights: Derives a definition of e-vehicle services from the concepts of service science. Defines three general e-vehicle service classes and all service types in each class. Reviews state-of-the-art approaches to realization of e-vehicle services. Shows key technology requirements and management decisions of e-vehicle services. Indicates the technologies and business models to be supported by policy measures. Abstract: Policymakers primarily rely on both subsidies and non-economic incentives to support the adoption of electric vehicles. Nevertheless one of the major barriers to widespread adoption is still given by consumer concerns about the economic benefit of electric vehicle ownership. In this work, we propose economic incentives to ownership in terms of electric vehicle services. We use the concepts of service science to propose a definition of e-vehicle service, and we identify microgrid operation, energy trading and vehicle sharing as general service contexts. We derive the service types within each context by reviewing state-of-the-art approaches to service realization. The resulting service classification provides a complete overview of opportunities to leverage the full economic potential of electric vehicles. As such it indicates which business models and technologies should be supported by policy measures to accelerate the adoption of electric vehicles.